Palmoplantar keratoderma (PPK): acquired and genetic causes of a not so rare disease. (September 2014) - Schiller, Stina; Seebode, Christina; Hennies, Hans Christian; Giehl, Kathrin; Emmert, Steffen
Summary Palmoplantar keratodermas (PPK) comprise a heterogeneous group of keratinization disorders with hyperkeratotic thickening of palms and soles. Sporadic or acquired forms of PPKs and genetic or hereditary forms exist. Differentiation between acquired and hereditary forms is essential for adequate treatment and patient counseling. Acquired forms of PPK have many causes. A plethora of mutations in many genes can cause hereditary PPK. In recent years several new causative genes have been identified. Individual PPK may be quite heterogeneous with respect to presentation and associated symptoms. Since the various hereditary PPK – like many other monogenic diseases – exhibit a very low prevalence, making of the correct diagnosis is challenging and often requires a molecular genetic analysis. Knowledge about the large but quite heterogeneous group of hereditary PPK is also important to dissect the molecular mechanisms of epidermal differentiation on palms and soles, ultimately leading to targeted corrective therapies in the future.